Exile : the sense of alienation in modern Russian letters - Patterson, David, 1948-
The life of a human community rests on common experience. Yet in modem life there is an experience common to all that threatens the very basis of community -- the experience of exile. No one in the modem world has been spared the encounter with homelessness. Refugees and fugitives, the disillusioned and disenfranchised grow in number every day. Why does it happen? What does it mean? And how are we implicated?David Patterson responds to these and related questions by examining exile, a primary motif in Russian thought over the last century and a half. By ""exile"" he means not only a form of pu.